Indonesia’s Public Diplomacy through Modest Fashion in Turkey - Elisa Kusumawardhani; Junita Budi Rahman; Akim Akim (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2022)
Indonesia’s modest fashion has proliferated in the last decade. It encourages Indonesia to become the center of the world’s modest fashion. In order to achieve this goal, Indonesia employs public diplomacy toward the global public and various countries, one of which is Turkey. However, the pandemic has limited international activities. This study examines Indonesia’s public diplomacy through modest fashion toward Turkey during the pandemic. This research was conducted with a qualitative descriptive method. Data collection techniques were carried out through a literature study. Meanwhile, the data analysis is carried out by reducing data, presenting data, and drawing conclusions. This study shows that Indonesian public diplomacy through modest fashion in Turkey is carried out with a strategic communication dimension through a hybrid fashion show (offline and online) with the theme of introducing modest fashion in Indonesia. It is done to adjust public diplomacy during the pandemic, so the message to be conveyed can be adequately achieved. The purpose of this public diplomacy is to build the image of Indonesia in a modest fashion and achieve economic interests by entering the Turkish market. Turkey Modest fashion Indonesia telah berkembang pesat dalam satu dekade terakhir. Hal ini mendorong Indonesia untuk menjadi pusat modest fashion dunia. Tujuan tersebut berusaha dicapai dengan diplomasi publik terhadap publik global dan berbagai negara, salah satunya adalah Turki. Namun, adanya pandemi membuat aktivitas internasional menjadi lebih terbatas. Penelitian ini bertujuan untuk mengkaji tentang diplomasi publik Indonesia melalui modest fashion terhadap Turki pada masa pandemi. Penelitian inidilaksanakan dengan metode deskriptif kualitatif. Teknik pengumpulan data dilakukan melalui studi pustaka. Sementara teknis analisis data dilaksanakan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini menunjukkan bahwa diplomasi publik Indonesia melalui modest fashion di Turki dilaksanakan dengan dimensi komunikasi strategis, yaitu melalui hybrid fashion show (ofine dan online) yang bertemakan pengenalan modest fashion Indonesia. Hal ini dilakukan untuk menyesuaikan diplomasi publik pada masapandemik agar pesan yang ingin disampaikan dapat tercapai dengan baik. Tujuan dari diplomasi publik ini adalah untuk membangun citra Indonesia dalam modest fashion dan meraih kepentingan ekonomi dengan memasuki pasar Turki.